Observation of the Epithelial Cell Behavior in the Nasal Septum During Primary Palate Closure in Mice - Yamamoto, Sayuri; Kurosaka, Hiroshi; Miura, Jiro; Aoyama, Gozo; Sarper, Safiye Esra; Oka, Ayaka; Inubushi, Toshihiro; Nakatsugawa, Kohei; Usami, Yu; Toyosawa, Satoru; Yamashiro, Takashi (Frontiers in Physiology, 2020)
Epithelial fusion is critical in palatogenesis and failed fusion results in a cleft at this junction. The bilateral secondary palatal processes fuse in the middle of the face to form the secondary palate. Later, the dorsal side of the secondary palatal shelves fuse to the nasal septum to complete palatogenesis. Importantly, the anterior border of the secondary palatal shelf fuses with the primary palate, which is located at the anterior and ventral border of the nasal septum. While numerous studies have investigated the mechanism of fusion between secondary palatal shelves, very little is known about how the primary palate touches and fuses with the secondary palatal shelves. In this study, we investigate the possible epithelial cell behaviors on the surface of the primary palate using palatal explant cultures of K14-GFP mice. A time-lapse observation of the GFP-labeled epithelium and an SEM analysis revealed that the bulging epithelium appeared at the region corresponding to the fusing area and expanded rostrally on the nasal septum surface in the absence of the secondary palatal processes. Unlike on the secondary palate surface, cellular migration and subsequent autonomous mesenchymal exposure were not evident on the nasal septum or the primary palate. TUNEL staining revealed that these bulging epithelia were undergoing apoptosis. These findings indicated that bulging with apoptosis was autonomously initiated at the presumptive region of the fusion without contact with the opposing secondary palate.